Desarrollo de un sistema informático para automatizar el proceso de registros médicos de la Clínica Odontológica osd Ortodoncia y salud dental aplicando prácticas ágiles. - Iza Quispe, Germánico Rafael (2022)
The OSD Orthodontics and Dental Health Dental Clinic currently has ineffective information management, information related to patients, medical appointments and account statements, its access generates delays in customer service, so that the clinic can have a Improvement in the organization of said information requires the implementation of a system which manages the information effectively. The objective of this project focuses on the elaboration and implementation of a computer system for the documentary and administrative management of the OSD Orthodontics and Dental Health Dental Clinic. How much time will the implementation of the computer system, the processes of preliminary medical records, appointment scheduling and consultation of outstanding balances reduce?